Synthesis of a Sunscreen Compound n-Octyl Para-Menthoxy Cinnamat using Ethyl Para-Methoxy Cinnamat Isolated from Kencur Tuber (Kaemferia galanga L.) as Raw Material - Nurul Hidajati; Suyatno Suyatno (Jurnal ILMU DASAR, 2008)
A sunscreen compound namely n-octyl para-methoxy cinnamat (OPMC) had been synthesized from the ethyl para-methoxy cinnamat (EPMC) isolated from the kencur tuber (Kaemferia galanga L.) as the raw material. The convertion of EPMC to OPMC was conducted by hydrolysis reaction of EPMC using the alcoholic KOH solution catalyst to yield para-methoxy cinnamat acid (PMCA). Futhermore, the esterification reaction of PMCA and n-octanol, using the concentrated sulfuric acid catalyst produced OPMC as a colorless needle crystal with rendemen 53.98%. The molecular structure of OPMC was identified by spectroscopic methods including UV, IR, 1H-NMR, and EIMS.